Internationalisation of healthcare: a fairer approach for local patients / Nuraisyah Chua Abdullah, Herwina Rosnan and Norzayana Yusof. - Abdullah, Nuraisyah Chua; Rosnan, Herwina; Yusof, Norzayana (Universiti Teknologi MARA Cawangan Selangor, 2019)
Malaysia is among the selected countries for medical tourism due to its excellent healthcare services. Nevertheless, there are concerns if service providers are balancing the local and foreign patients' healthcare demands due to the similarities and differences of their behaviour on these two groups. Through literature analysis, it is found the lack of discussion on medical practitioners' behaviour towards local patients, this paper aims to analyse the that unhealthy behaviour towards local patients is profound. Hence, the discussions are hoped to spark the policy-makers' attention in restructuring the healthcare policy to realign the medical practitioners' behaviour on both patient groups.